2020
DOI: 10.21608/ejchem.2020.20809.2251
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate Scaffold Derived Hydrazide-Hydrazones: Synthesis and Antioxidant Activities

Abstract: A NEW series of Bezafibrate derived hydrazide-hydrazone analogues were generated by using some five membered, fused heterocyclic and aromatic aldehydes. All the hydrazones were obtained in good yields from methanol at 60-80 °C for 5-8 hours stirring. Moreover, the compounds were also screened for their anti-oxidant activity potentiality at four different concentrations using DPPH method. Among these compounds, compound 6k analogue of bezafibrate was found to be the most active at all the tested concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The review of scientific literature proved a wide range of potential applications and beneficial therapeutic effects of compounds containing hydrazone moiety, like hydrazidehydrazones or sulphonyl hydrazones [11,13,15,16,18]. The results of much research, including those carried out by our research group, indicated that molecules containing hydrazone moiety are cytotoxic and cytostatic towards neoplastic cells [18,22,23].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The review of scientific literature proved a wide range of potential applications and beneficial therapeutic effects of compounds containing hydrazone moiety, like hydrazidehydrazones or sulphonyl hydrazones [11,13,15,16,18]. The results of much research, including those carried out by our research group, indicated that molecules containing hydrazone moiety are cytotoxic and cytostatic towards neoplastic cells [18,22,23].…”
Section: Discussionmentioning
confidence: 87%
“…These substances are also distinguished by numerous properties which are important from the medical and pharmaceutical point of view. The biological activity of compounds from sulphonyl hydrazone and hydrazide-hydrazone group described so far includes antimicrobial, anti-tuberculosis, anti-HIV, anticonvulsant, analgesic, anti-inflammatory, antioxidant, antidepressant, and most importantly, from the point of view of this work-anticancer activity [9][10][11][12][13][14][15][16][17]. In our recently published study, the newly-synthesized benzenesulphonyl hydrazones demonstrated the antiproliferative potential towards three human cancer cell lines: renal cell carcinoma (769-P), liver cancer (HepG2) and lung squamous cell carcinoma (H2170).…”
Section: Introductionmentioning
confidence: 98%
“…To the best of our knowledge, this is the first report in experimenting with carboxylic acid functionality in the GBP scaffold. Further, the authors have also previously reported some antibacterial [16,17] and antioxidant [18] hydrazide-hydrazone molecules. In continuation to it, authors have explored antimicrobial activities of the novel gabapentin hydrazide-hydrazone analogues along with antioxidant activity of interest.…”
Section: Introductionmentioning
confidence: 98%